Paul within judaism: perspectives on Paul and Jewish identity - Bird, Michael; Bühner, Ruben A.; Frey, Jörg; Rosner, Brian S. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2023)
This conference volume features cutting edge research from an international cohort of scholars on the still-controversial debates regarding Paul's relationship with Judaism. Taken together, the contributions represent a sympathetic but critical assessment of the Paul within Judaism approach to Pauline interpretation. They take up many of the key questions germane to the debate, including different perspectives on Jewish identity, ethnicity, Torah-observance, halakha, the relationship between Jewish and non-Jewish followers of Christ, and the contested character of Jewish identity in antiquity. By combining a broad swath of both German- and English-language scholarship, the volume attempts to bring different perspectives into conversation with each other